2015
DOI: 10.1039/c5dt00075k
|View full text |Cite
|
Sign up to set email alerts
|

Efficient uptake of dimethyl sulfoxide by the desoxomolybdenum(iv) dithiolate complex containing bulky hydrophobic groups

Abstract: A desoxomolybdenum(IV) complex containing bulky hydrophobic groups and NH···S hydrogen bonds, (Et4N)[Mo(IV)(OSi(t)BuPh2)(1,2-S2-3,6-{(4-(t)BuC6H4)3CCONH}2C6H2)2], was synthesized. This complex promotes the oxygen-atom-transfer (OAT) reaction of DMSO by efficient uptake of the substrate into the active center. The clean OAT reaction of Me3NO is also achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…On the other hand, the solution of (LuH) 2 [ 1 ] in [D 8 ]toluene was green and exhibited broad 1 H NMR signals, suggesting the presence of paramagnetic molybdenum(V) species (Figure ). As shown in Figure , the absorption spectrum of this complex in toluene exhibited an absorption maximum at 756 nm, which is characteristic of [Mo V O( L ) 2 ] – . Interestingly, the intensity of the absorption indicated that [Mo IV O( L ) 2 ] 2– was converted quantitatively into [Mo V O( L ) 2 ] – .…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…On the other hand, the solution of (LuH) 2 [ 1 ] in [D 8 ]toluene was green and exhibited broad 1 H NMR signals, suggesting the presence of paramagnetic molybdenum(V) species (Figure ). As shown in Figure , the absorption spectrum of this complex in toluene exhibited an absorption maximum at 756 nm, which is characteristic of [Mo V O( L ) 2 ] – . Interestingly, the intensity of the absorption indicated that [Mo IV O( L ) 2 ] 2– was converted quantitatively into [Mo V O( L ) 2 ] – .…”
Section: Resultsmentioning
confidence: 95%
“…The absorption spectra of the reaction mixture after 6 min are shown in Figure S9. The absorption spectral change for the reaction of (Et 3 NH) 2 [ 1 ] with two equivalents of Me 3 NO showed a rapid increase of both [ 2 ] 2– (at 398 and 560 nm) and [Mo V O( L ) 2 ] – (at 756 nm), followed by the immediate disappearance of [Mo V O( L ) 2 ] – . The resulting spectrum resembles that of the decomposed compound shown in Figure S8b, suggesting the dissociation of the ligand.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A weak and broad absorption band was observed at 770 nm during the catalytic reaction (Fig. 5), which suggests the presence of a monooxomolybdenum(V) species 23,29,30 generated by one-electron reduction as a side reaction.…”
Section: Catalysis In An Aqueous Micellar Solutionmentioning
confidence: 99%
“…In their experiments, Ueyama et al found an accelerated addition of the oxygen of TMAO to the [Mo IV O(2N-bdt)2] 2− complex in contrast to the non-substituted related benzene-1,2-dithiolate-derived complexes introduced by Garner In the other type of half cycle reaction, a substrate donates its oxo function as an oxygen atom to the metal ion center accompanied by the oxidation of M IV to M VI . Respective OAT donor reagents/substrates are often derived from trimethylamine-N-oxide (TMAO) since this is actually also a natural substrate for TMAO reductase, or dimethylsulfoxide (DMSO), as in the DMSO reductase enzyme [30,33,51,52]. In 2006, Ueyama and others designed a novel aromatic dithiolene ligand 1,2-S 2 -3-R-CONHC 6 H 3 (2N-bdt; R=CH 3 , t Bu, CF 3 , CPh 3 , C(C 6 H 4 -4-t Bu) 3 ) (Figure 6b), bearing two amide moieties adjacent to the dithiolene in order to enable intramolecular hydrogen bonding in their complexes since H bonds play important roles for the enzymes' active sites and reactivities [53].…”
Section: Dithiolene Complexesmentioning
confidence: 99%